2011
DOI: 10.1037/a0022675
|View full text |Cite
|
Sign up to set email alerts
|

When managers and their teams disagree: A longitudinal look at the consequences of differences in perceptions of organizational support.

Abstract: The authors argue that over time the difference between team members' perception of the organizational support received by the team (or team climate for organizational support) and their manager's perception of the organizational support received by the team has an effect on important outcomes and emergent states, such as team performance and team positive and negative affect above and beyond the main effects of climate perceptions themselves. With a longitudinal sample of 179 teams at Time 1 and 154 teams at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
154
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(165 citation statements)
references
References 99 publications
(162 reference statements)
10
154
0
1
Order By: Relevance
“…This is a novel finding insofar as the indirect effect of leader-team value congruence on team effectiveness has received limited theoretical attention, as compared with that given to the direct effects of leader-team perceptual congruence on team outcomes (e.g., Bashshur et al, 2011;Gibson et al, 2009). Put differently, our results shed some light on the intervening mechanisms that help to explain how and why value alignments associated with power distance can have positive consequences on team effectiveness.…”
Section: Theoretical Implicationsmentioning
confidence: 64%
See 2 more Smart Citations
“…This is a novel finding insofar as the indirect effect of leader-team value congruence on team effectiveness has received limited theoretical attention, as compared with that given to the direct effects of leader-team perceptual congruence on team outcomes (e.g., Bashshur et al, 2011;Gibson et al, 2009). Put differently, our results shed some light on the intervening mechanisms that help to explain how and why value alignments associated with power distance can have positive consequences on team effectiveness.…”
Section: Theoretical Implicationsmentioning
confidence: 64%
“…We therefore join Gibson et al (2009) in calling for an expanded view of the leader-team interface (see also Bashshur et al, 2011), one that pays specific attention to the role of normatively desirable behaviors (i.e., values) from multiple stakeholders' point of view. It is thus hoped that the present investigation offers a springboard for future research and meaningful input for the accumulation of evidence in this area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea has heen partially demonstrated in the context of forming project teams and alliance building (Janicik & Larrick, 2005) and in work teams (Bashshur, Hernandez, & Gonzalez-Roma, 2011), but more research examining moderators is needed. For example, there may be situations in which individuals' accurate or realistic perceptions of system negation could actually distract them from their own goal striving.…”
Section: Dynamic Network Intelligence and Cognitive Accuracymentioning
confidence: 99%
“…One important consequence for individuals who have high CIS but assimilate is the negative effect on their psychological wellbeing as indicated by feelings of anxiety, tension, and other unpleasant emotions (Bashshur, Hernandez, & Gonzalez-Roma, 2011). Furthermore, identity research has suggested that identity-disconfirming events can have adverse psychological and health-related consequences (Swann, Johnson, & Bosson, 2009;Wood et al, 2005), which has telling implications for individuals who feel pressured into assimilating when CIS is high.…”
Section: High Cultural Identity Saliencementioning
confidence: 99%